ADMET Prediction Compounds of Polar Extract Curcuma rhizoma - Sumardi Sumardi; Suprianto Suprianto; Suci Rahmadani Siregar; Arifin Putra Zai; Regina Elianda Tambubolon; Fridelly Mairani (Jurnal Indah Sains dan Klinis, 2024)
The pharmacokinetic and metabolic profiles of polar extract compounds from Curcuma rhizoma were evaluated using ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) predictions. Most compounds exhibited high gastrointestinal (GI) absorption, with the exception of D-glucose, citric acid, and terpenoids such as alpha-pinene and zingiberene, which demonstrated low absorption, highlighting potential challenges for systemic bioavailability. Blood-brain barrier (BBB) permeability was observed in lipophilic compounds like xanthorrhizol, bisdemethoxycurcumin, and terpenoids, suggesting their potential for CNS-targeted therapies, while polar compounds, including D-glucose, citric acid, and most curcuminoids, were non-permeant. D-glucose was the only compound identified as a P-glycoprotein (Pgp) substrate, indicating minimal efflux-related limitations for other compounds. Selective cytochrome P450 (CYP) enzyme inhibition was detected in compounds such as xanthorrhizol, curcuminoids, and zingiberene, suggesting potential metabolic interactions in multi-drug contexts. Promising therapeutic candidates include curcuminoids and xanthorrhizol, while non-BBB-permeant and low-absorbing compounds may require formulation strategies or alternative applications. These findings provide valuable insights into the pharmacological optimization of Curcuma rhizoma compounds, offering a foundation for further research in drug discovery and development.